Evaluasi Kinerja Sistem Informasi Perpustakaan (SIPRUS) menggunakan Analisis PIECES Ditinjau dari Persepsi Pustakawan (Studi Kasus Perpustakaan UIN Sunan Kalijaga Yogyakarta) - Sri Wahyuni (Universitas Wijaya Kusuma Surabaya, 2020)
In 2004, the library of UIN Sunan Kalijaga used the Library Information System (SIPRUS) designed by PT. PJI. This system integrates various library sub-systems, for example, Self-service, OPAC, circulation, library processing, and digital repositories. This study discusses how to find information about the system, so an evaluation is needed that provides information about how the program works, and how to discuss problems that can interfere with the implementation of the user's viewing activities. This type of research is an evaluative descriptive study using cross-sectional, which provides an opinion about the user's assessment of the information system currently running in the library of UIN Sunan Kalijaga. Interviews, documentation, and observation are used to collect the data. Data analysis in this study uses reduction data, presentation data, and verification (concluding). Researchers used PIECES (Performance, Information, Economy, Control, Effectiveness, and Service) analysis to get more indicators. The results from this CYPRUS are very helpful in the field of material processing library and also too easy to launch the work administratively. It is probably able to run effectively and efficiently.Keyword: Library, PIECES Analysis, SIPRUS